EFEKTIVITAS PROBLEM-FOCUSED COPING DAN EMOTION FOCUSED COPING TERHADAP STRESS KERJA : SEBUAH KAJIAN LITERATUR - Angelina Amanda Dewi; Dimas Aryo Wicaksono (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
Job stress is an inevitable part of employees' lives. Every employee has a strategy in dealing with the stressors they experience. The purpose of this study was to determine the effective coping of stress in dealing with employee stress at work. The design used is a literature review of articles collected through journal providers, namely Science Direct, EBSCOHOST, and Google Scholar. Based on the articles that have been collected, it was found that the use of coping, whether it is emotional-focused coping or problem-focused coping will depend on the cause of stress, type of work, and individual reactions that vary when dealing with problems. Therefore, it is necessary to pay attention to the special characteristics of each job and to respect individual characteristics.